Answer:
f(x) should shifted Right by 4 units to obtain g(x) ⇒ B
Explanation:
Let us put g(x) in the form of g(x) = (x - h)² + k, where h is the the horizontal shift (x - h) to right, (x + h) to left and k is the vertical shift (k) up and (-k) down
In the quadratic function y = ax² + bx + c, h =
and k = y at x = h
∵ g(x) = x² - 8x + 1
∵ a is the coefficient of x² and b is the coefficient of x
∴ a = 1 and b = -8
∵ h =
![-(b)/(2a)](https://img.qammunity.org/2021/formulas/mathematics/high-school/o19e1oplxctl0e9dhldd45v0kb1qiu1tcy.png)
∴ h =
![-(-8)/(2(1))=(8)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/td17lqiwfzczqe8141st5lu8iqsu9a4nn7.png)
∴ h = 4
∵ k = g(x) at x = h
- Substitute x by 4 in g(x) to find k
∴ k = (4)² - 8(4) + 1 = 16 - 32 + 1
∴ k = -15
- Substitute them in the form of g(x) = (x - h)² + k
∴ g(x) = (x - 4)² + (-15)
∵ h is the horizontal shift
∵ (x - h) means shift to right h units
∵ f(x) = x²
∵ g(x) = (x - 4)² + (-15)
- That means f(x) is shifted 4 units to the right
∴ f(x) should shifted right by 4 units to obtain g(x)